Étude des législations minières groenlandaises (1932-2021) : indépendantisme minier, usages des terres et conflits sociaux - Pia Bailleul (Centre de Recherches sur les Mondes Américains, 2021)
In 2009, Greenland's autonomy is reinforced by pro-independence legislation. This law states the handing over of all political power to the island and in particular authority over land, until then under the Danish government. It sets the conditions for the autonomy of the national, until then partially funded by Denmark. Danish grants were to be replaced by revenues from the mining industry, thus bringing Greenland to full independence. Since 2009, the mining sector has been strengthened by laws aiming towards developing its industrial side and nationalizing the land. These developments gave rise to a national mobilization leading to “indigenous” and “citizenship” claims in an unprecedented way. I consider these political categories as symptoms of a disturbance of national cohesion by the new territorial and industrial measures taken in favor of developing the mining sector. This article explores the characteristics and implications of associating a national independence project with a legislation that fosters the development of industrial mining, and analyzes political disturbance as revealing of a transformation in land management and uses.